2007
DOI: 10.3748/wjg.v13.i13.2011
|View full text |Cite
|
Sign up to set email alerts
|

Development of multiple myeloma in a patient with gastrointestinal stromal tumor treated with imatinib mesylate: A case report

Abstract: .In some rare cases coexistence of GIST with other malignancies has been reported [2][3][4][5][6] . Here we describe a case of a 74-year old male with GIST who developed multiple myeloma (MM) during the course of GIST treatment. To the best of our knowledge, the co-existence of GIST and multiple myeloma has not been reported so far. Case reportA 74-year old male was presented complaining of dyspepsia. Clinical examination revealed a palpable epigastric mass, with no other abnormal clinical findings. Computed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, MM was reported to have developed in an IM-treated patient with a gastrointestinal stromal tumor [11]. These laboratory and observational findings might suggest that IM facilitates the development of MM.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, MM was reported to have developed in an IM-treated patient with a gastrointestinal stromal tumor [11]. These laboratory and observational findings might suggest that IM facilitates the development of MM.…”
Section: Discussionmentioning
confidence: 79%
“…In the literature, 8 of the nine patients who first had CML received Imatinib before MM was diagnosed. Moreover, it has been reported that an imatinib-treated patient developed MM after a gastrointestinal stromal tumor [ 12 ]. It can be proposed that imatinib mesylate treatment may promote the development of MM.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, three of the four patients who first had CML and then MM received imatinib mesylate before MM was diagnosed [5][6][7]. Furthermore, MM was reported to have developed in an imatinib mesylate-treated patient with a gastrointestinal stromal tumor [26]. These clinical observations suggest that imatinib mesylate treatment may promote the development of MM.…”
Section: Discussionmentioning
confidence: 99%